"Mal-estar" e laço social nas organizações empresariais: um estudo de caso - Barati, Guilherme Henrique Lima (2007)
This investigation examines the social relationships or bonds formed by subjects inside corporate institutions, within the context of discontentment , which a capitalistic society experiences contemporaneously. To approach this theme, psychoanalytic delineations such as epistemic, methodololgic, and ethical were considered. It was sought to articulate the subject s singular positioning and social questions in general related to capital, work organization, and discontentment in culture. The exposition is dedicated initially to the psychoanalytical conception of how to establish the relationship between subject and society. The conceptual framework is drawn from both Freud s social works and Lacan s Four Discourses . The discontentment and the injunction of enjoyment (jouissance) will be shown as a consequence of social bonds. Sequentially, psychoanalytical concepts of discontentment , enjoyment (jouissance), and supplementary enjoyment and the suppositions offered by capitalism s social sciences, are sought. Initially, the question of work in contemporary society, and the submission of the subject to capitalistic imperatives through the ideology in different cases and institutions are approached. Further, the contradictions and ruptures related to these imperatives is brought forward and considered. The workers reordering of subjectivity takes form in everyday life through the ways of work organization. The work, in contemporary terms, shows itself manifested through an instable and complex technological environment. Working conditions in third world countries are found to be increasingly more precarious. The aforementioned theoretical structure underlines the path of the worker in the form of a case study